“Pharmaceutico Analytical Standardization And Antimicrobial Evaluation Of Purandar Vati In The Management Of Kasa”- A Protocol Article - Sharma, Kulbhushan; Kumar Bhatt, Avadhesh (Journal of Neonatal Surgery, 2025)
Background: Kasa (cough) is a commonly encountered respiratory disorder described extensively in Ayurvedic texts. In modern medicine, it is often associated with microbial infections of the upper and lower respiratory tract, commonly caused by Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenzae, etc. Due to rising antibiotic resistance, traditional formulations such as Purandar Vati, a herbomineral preparation described in Bhaishajya Ratnavali, offer promising alternatives for management. Aim:To evaluate the Pharmaceutico-analytical profile and in vitro antimicrobial efficacy of Purandar Vati in the management of Kasa. Objectives: To prepare Purandar Vati following classical Ayurvedic methods and To analyze the formulation through standard analytical parameters To assess antimicrobial activity against selected respiratory pathogens. Materials and Methods: Purandar Vati will be prepared using classical guidelines from Bhaishajya Ratnavali, comprising Shuddha Parada, Shuddha Gandhaka, Trikatu, Triphala, and Aja Ksheera as Bhavana Dravya. Analytical parameters including organoleptic, physicochemical tests (LOD, pH, ash values, etc.), TLC profiling, and microbial load will be carried out as per CCRAS protocol. The in vitro antimicrobial activity will be tested against six common respiratory tract pathogens using agar diffusion and MIC methods. Results: Results will be observed as per zones of inhibition against Staphylococcus aureus, Streptococcus pyogenes, Klebsiella pneumoniae, and Haemophilus influenzae. Discussion: It will be discussed on the basis of results whether it can serve as a potential adjunct or alternative in the treatment of microbial respiratory infections associated with Kasa